The extended-view totally extraperitoneal (eTEP) approach for Ventral hernia: Short-term results from a single center - Tomtong, Ronnayong; Pumwiset, Noppadol; Saechua, Potchara; Khaimook, Araya (Journal of the Association of General Surgeons of Thailand under the Royal of Patronage of HM the King, 2025)
Background The eTEP technique is a popular approach in abdominal wall hernia surgery in recent years. This study aims to present the results of applying minimally invasive treatment with the laparoscopic eTEP approach for abdominal wall hernias. Methods This study is a retrospective review of 21 patients who underwent laparoscopic eTEP for primary abdominal wall hernias and incisional hernias between July 2022 and February 2024 (median follow up of 6.5 months) Result A total of 21 patients underwent the laparoscopic eTEP approach. 6 patients (28.5%) had primary hernias and 15 patients (71.4%) had incisional hernias. The mean hospital stay was 3.8 days. There were two cases of recurrence after discharge. Conclusion The laparoscopic eTEP approach provides advantages such as less postoperative pain, shorter hospital stays, early return to work, and fewer surgical complications. However, the laparoscopic eTEP technique has a long operative time and requires advanced laparoscopic suturing skills